2002
DOI: 10.1073/pnas.092089799
|View full text |Cite
|
Sign up to set email alerts
|

cAMP facilitates EDHF-type relaxations in conduit arteries by enhancing electrotonic conduction via gap junctions

Abstract: We have investigated the role of cAMP in NO-and prostanoidindependent relaxations that are widely attributed to an endothelium-derived hyperpolarizing factor (EDHF). Under control conditions EDHF-type relaxations evoked by acetylcholine (ACh) in rabbit iliac arteries were transient, but in the presence of the cAMP phosphodiesterase inhibitor isobutylmethylxanthine (IBMX) or the cell permeant cAMP analog 8-bromo-cAMP, relaxations became sustained with their maxima potentiated Ϸ2-fold. Relaxation was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 38 publications
1
109
0
1
Order By: Relevance
“…Hemoglobin was obtained by lysis of red cells in HPLC grade water and purified on a Sephadex G25 column. In further experiments with endothelium-denuded rings in the presence of L-NAME and indomethacin, cumulative concentration-relaxation curves were constructed for xanthine in the presence of 100 milliunits͞ml of xanthine oxidase (XO) and for H 2 O 2 after incubation with catalase (2,000 units͞ml), superoxide dismutase (500 units͞ml; xanthine curve only), the K v channel blocker 4-aminopyridine (300 M), the SK Ca and IK Ca ͞BK Ca channel blockers apamin and charybdotoxin in combination (100 nM each), the K ATP channel blocker glibenclamide (10 M), the soluble guanylyl cyclase inhibitor 1H- [1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one (ODQ, 10 M), the adenylyl cyclase inhibitor 2Ј,5Ј-dideoxyadenosine (2Ј,5Ј-ddA, 500 M), and the cell-permeant iron chelator 1,2 dimethyl-3-hydroxypyridin-4-one (deferiprone, 1 mM; xanthine curve only). All agents were obtained from Sigma, except 2Ј,5Ј-ddA (Affiniti, Nottingham, U.K.) and deferiprone (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemoglobin was obtained by lysis of red cells in HPLC grade water and purified on a Sephadex G25 column. In further experiments with endothelium-denuded rings in the presence of L-NAME and indomethacin, cumulative concentration-relaxation curves were constructed for xanthine in the presence of 100 milliunits͞ml of xanthine oxidase (XO) and for H 2 O 2 after incubation with catalase (2,000 units͞ml), superoxide dismutase (500 units͞ml; xanthine curve only), the K v channel blocker 4-aminopyridine (300 M), the SK Ca and IK Ca ͞BK Ca channel blockers apamin and charybdotoxin in combination (100 nM each), the K ATP channel blocker glibenclamide (10 M), the soluble guanylyl cyclase inhibitor 1H- [1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one (ODQ, 10 M), the adenylyl cyclase inhibitor 2Ј,5Ј-dideoxyadenosine (2Ј,5Ј-ddA, 500 M), and the cell-permeant iron chelator 1,2 dimethyl-3-hydroxypyridin-4-one (deferiprone, 1 mM; xanthine curve only). All agents were obtained from Sigma, except 2Ј,5Ј-ddA (Affiniti, Nottingham, U.K.) and deferiprone (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanisms of relaxation activated by these agents may involve different pathways. In rabbit arteries, NO͞prostanoid-independent relaxations to ACh are attenuated by connexin (Cx)-mimetic peptides and glycyrrhetinic acid derivatives that interrupt gap junctional communication, whereas analogous responses to A23187 are insensitive to such inhibitors (1)(2)(3)(4)(5). By contrast, ''sandwich'' bioassay studies with closely apposed endothelium-intact and -denuded strips of rabbit superior mesenteric or ilio-femoral artery demonstrate that A23187, but not ACh, promotes the release of a diffusible factor that is capable of causing relaxation (2,5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that calcein remained concentrated within the endothelial cells, including the endothelial cell projections which form gap junctions with the muscle, strongly suggests that the dye normally leaves the endothelium via gap junctions (and/or possibly connexin hemichannels) [42]. This technique has been used previously to show the effectiveness of another group of gap junction uncoupling agents, the connexin mimetic gap peptides [43].…”
Section: Regulation Of Endothelial Ca 2+ Events Via Myoendothelial Gamentioning
confidence: 98%
“…8 A recently published study by Taddei et al 9 has reported that ACh responses in the forearm of subjects with EH are sensitive to intra-brachial infusions of sulphaphenazole, an inhibitor of cytochrome P450 epoxygenase (CYP2C9). 9 On the basis of these data, these investigators suggest that a CYP2C9 product (11,12 epoxyeicosatrienoic acid (11,12 EET)) plays a key role in human EH as an endothelium-derived hyperpolarizing factor (EDHF) producing rapid compensatory vasorelaxation under conditions of decreased NO bioavailability. 9 The EDHF is a complex and multifaceted response, [10][11][12][13][14][15][16] playing a particularly prominent role in smaller resistance-sized vessels.…”
Section: Introductionmentioning
confidence: 99%